Long-Range Hexagonal Arrangement of TiO2 Nanotubes by Soft Lithography-Guided Anodization. (10th June 2016) - Vega, V.; Montero-Moreno, J.M.; García, J.; Prida, V.M.; Rahimi, W.; Waleczek, M.; Bae, C.; Zierold, R.; Nielsch, K.
Graphical abstract: Scanning electron micrograph showing the highly hexagonally long-range ordering of the TiO2 nanotubes array after following combined steps of Laser Interference Lithography pre-patterning and further electrochemical anodization procedure. Upper inset displays the TEM cross-section view of a pair of freestanding TiO2 nanotubes, where it can be appreciated their dimensions. Highlights: A novel strategy based on combined methods of Laser Interference Lithography and electrochemical anodization is developed for the fabrication of nanostructures. As a proof of concept, the synthesis of long-range hexagonally ordered TiO2 nanotube arrays is demonstrated. TiO2 nanotubes having 32 nm of inner diameter, around of 25 nm in wall thickness and 210 nm of lattice parameter were anodically grown under proper synthesis conditions. Abstract: Long range hexagonally ordered TiO2 nanotube arrangements have been synthesized by employing a novel strategy consisted of combining the well-known Laser Interference Lithography technique together with electrochemical anodization methods. By properly tuning the fabrication parameters that make match between both techniques, TiO2 nanotube arrays having near 32 nm of inner diameter, wall thickness around of 25 nm and 210 nm of lattice parameter were anodically grown on pre-patterned Ti foils over large sample surface areas, typically of several squared centimetres in size. This opens the possibility to the development of new types of functional devices based on self-organized morphologies of anodic TiO2 nanotubes, requiring both high spatially ordered and defect-free nanotube arrangements.